An experimental insight into dynamic characteristics and wear of centrifugal pump handling multi-size particulate slurry. (August 2022) - Wang, Yong; Wang, Xiaolin; Chen, Jie; Li, Gangxiang; Liu, Houlin; Xiong, Wei
Highlights: The energy performance, dynamic characteristics and wear of centrifugal pump handling multi-size particulate slurry were studied. Based on multi-size particulate slurry, the wear characteristics of centrifugal pump were investigated with the paint wear method. The phenomena and laws of pulsation, vibration and wear of centrifugal pump with different flow rates and sand concentrations were discussed. Abstract: The river water has a high sand content and the characteristics of mixed distribution of sand particles with different diameters. The effect of sand particles on the dynamic characteristics and wear of centrifugal pumps is an important issue when handling particulate slurry. The objective of this work is to establish the effect of flow rate and sand volume concentration variation on pump energy performance, outlet pressure pulsation, pump body vibration, and pump impeller wear. Experiments were conducted in a pilot plant test rig with five flow rates and three particle concentrations based on multi-size particulate slurry. It was observed that the head and efficiency of the centrifugal pump decrease with the increase of sand concentration, whereas the effect of small sand concentration on the energy performance of the pump is weak. The larger the flow rate of centrifugal pump, the lower the pressure pulsation and vibration intensity of pump body, but the more serious the impeller wear. When the sediment concentration increases, the pressure pulsation at the pump outlet and the vibration intensity of the pump body increase, and the impeller wear is more serious. In addition, with the increase of pump operation time, the outlet of blade pressure surface, the middle area of blade suction surface and the outlet area of impeller back shroud passage are seriously worn, and the outlet of blade pressure surface is the most serious.